SEKILAS KAJIAN APLIKASI PERPUSTAKAAN DIGITAL BERBASIS OPEN SOURCE - Suyanto, Agus (Jurnal Ilmu Budaya, 2012)
As information institution which develops fast, libraiy shows its development from its application of information technology, starting from conventional library, automated library to digital library. The usage and development of digital library should use software as tools of collecting, processing and distributing processes used by users. There are some digital library softwru·es from the conunercial ones up to the open source. Considering the high prize of commercial software and,the limited budget of a library, it needs reconsideration and wise choice. The appearance of OSS (Open Source Sofrware) which is free can be good solution for libraries such as Ganeha Digital Library, Greenstone, DSpace, and Eprints in creating and developing digital library.